Symptoms of psychosis in schizophrenia, schizoaffective disorder, and bipolar disorder: A comparison of African Americans and Caucasians in the Genomic Psychiatry Cohort. Issue 4 (11th December 2015) - Perlman, Greg; Kotov, Roman; Fu, Jinmiao; Bromet, Evelyn J.; Fochtmann, Laura J.; Medeiros, Helena; ,; Pato, Michele T.; Pato, Carlos N.
Abstract : Several studies have reported differences between African Americans and Caucasians in relative proportion of psychotic symptoms and disorders, but whether this reflects racial bias in the assessment of psychosis is unclear. The purpose of this study was to examine the distribution of psychotic symptoms and potential bias in symptoms assessed via semi‐structured interview using a cohort of 3, 389 African American and 5, 692 Caucasian participants who were diagnosed with schizophrenia, schizoaffective disorder, or bipolar disorder. In this cohort, the diagnosis of schizophrenia was relatively more common, and the diagnosis of bipolar disorder and schizoaffective disorder‐bipolar type was less relatively common, among African Americans than Caucasians. With regard to symptoms, relatively more African Americans than Caucasians endorsed hallucinations and delusions symptoms, and this pattern was striking among cases diagnosed with bipolar disorder and schizoaffective‐bipolar disorder. In contrast, the relative endorsement of psychotic symptoms was more similar among cases diagnosed with schizophrenia and schizoaffective disorder‐depressed type. Differential item function analysis revealed that African Americans with mild psychosis over‐endorsed "hallucinations in any modality" and under‐endorsed "widespread delusions" relative to Caucasians. Other symptoms did not show evidence of racial bias. Thus, racial bias in assessment of psychotic symptoms does not appear to explain differences in the proportion of symptoms between Caucasians and African Americans. Rather, this may reflect ascertainment bias, perhaps indicative of a disparity in access to services, or differential exposure to risk factors for psychosis by race. © 2015 Wiley Periodicals, Inc.